Análise do eletrocardiograma em adultos brasileiros: estudo longitudinal de saúde do adulto (ELSA-Brasil) - Marcelo Martins Pinto Filho (2016)
INTRODUCTION: The electrocardiogram (ECG) is a widely used tool in epidemiological studies, but there are few population-based studies in Latin America and Brazil. The Longitudinal Study of Adult Health (ELSA-Brasil), which included 15,105 participants (35-74 years) in six Brazilian capitals, allowed the creation of an electrocardiographic database of that population. The aim of this study is to describe the electrocardiographic measures in Brazilian adults absent of cardiovascular disease and evaluate the major electrocardiographic abnormalities, according to the Minnesota code, gender, age, race, and cardiovascular risk factors. METHODS: Cross-sectional study in which data from 14424 adultswere obtained (45.8% men, age 35-74 years) at baseline of ELSA-Brasil, through interviews and clinical and laboratory tests. The ECGswere recorded with the Burdick Atria 6100 machine and stored at the Pyramis System. Coding was automatic, according to the Minnesota coding system by the Glasgow Nursery software andreviewed manually. The distribution of electrocardiographic measurements in patients free of cardiovascular disease and who declared the race (n = 11,094, 44.5% men) were described as median (interquartile range). The prevalence of the major electrocardiographic abnormalities were described and stratified by sex, age group, race and number of cardiovascular risk factors. To compare the groups, we used the chi-square test. RESULTS: The mediansof the analyzed electrocardiographic measurements were, for men and women, respectively: heart rate 63x66bpm, PR interval 164x158ms, QTc interval 410vs421ms, QRS duration 92x86ms, P wave duration 112vs108ms, P wave axis 54vs57, R wave axis 35vs39 and T wave axis 39x45, with a significant difference between men and women for all variables (p <0.001 for all). The prevalence of major abnormalities was higher in men than in women (11.3 x 7.9%, p <0.001, OR = 1.5 [95% CI 1.33 to 1.66]). These findings were consistent across different age groups, race and number of cardiovascular risk factors. There was a significant increase in the prevalence of major electrocardiographic abnormalities with increasing age and number of cardiovascular risk factors(p <0.001 for both). With regards to race, the major electrocardiographic abnormalities were more prevalent in blacks, both for men (15.1% for blacks, 10.4% for mixed race, 11.1% for whites, p = 0.001) and for women (10% for blacks, 7.6% for mixed race, 7.2% for white, p = 0.004). CONCLUSIONS: The values for the described electrocardiographic measures can be used as a reference for healthy Brazilian adults without prevalent cardiovascular disease, stratified by sex. The prevalence of electrocardiographic abnormalities vary with age, gender, race and number of cardiovascular risk factors, reflecting the higher prevalence of cardiovascular disease in the elderly, in men, individuals of black race and those with higher number of cardiovascular risk factors.